2016
DOI: 10.1111/andr.12146
|View full text |Cite
|
Sign up to set email alerts
|

The Klinefelter syndrome is associated with high recurrence of copy number variations on the X chromosome with a potential role in the clinical phenotype

Abstract: SUMMARYThe Klinefelter syndrome (KS) is the most frequent sex chromosomal disorder in males, characterized by at least one supernumerary X chromosome (most frequent karyotype 47,XXY). This syndrome presents with a broad range of phenotypes. The common characteristics include small testes and infertility, but KS subjects are at increased risk of hypogonadism, cognitive dysfunction, obesity, diabetes, metabolic syndrome, osteoporosis, and autoimmune disorders, which are present in variable proportion. Although p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 36 publications
1
27
2
2
Order By: Relevance
“…LEP and EPO appear relevant to the increased prevalence of at least diabetes and obesity in KS patients (43) and might be used as biomarkers for the clinical management of KS in the future. An interesting observation was that both LEP and LEPR were down-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…LEP and EPO appear relevant to the increased prevalence of at least diabetes and obesity in KS patients (43) and might be used as biomarkers for the clinical management of KS in the future. An interesting observation was that both LEP and LEPR were down-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of CNVs, Rocca et al found that this region is associated with the phenotypes of the Klinefelter syndrome (KS) [37], which has a wide range of phenotypes. The common characteristics include small testes and infertility, but KS subjects are at increased risk of hypogonadism, cognitive dysfunction, obesity, T2D, osteoporosis, and autoimmune disorders [38].…”
Section: Discussionmentioning
confidence: 99%
“…In this report of over 21,000 cases, CNVs were found in various locations throughout the genome, but also included 2 Mol Neuropsychiatry 2018;4:83-89 DOI: 10.1159/000491489 significant duplications on Xq28 (one of which was in MAGEA11) and suggestive, although not significant, deletions on Xp21.2 (DMD). It is also interesting that a study of CNVs in Klinefelter's individuals [62] showed an overall increase in CNVs when compared with normal males or females, and half of the X-linked CNVs fell within regions encompassing genes. Most of these genes (90%) escape X inactivation and are within the regions of X-Y homology, particularly the pseudoautosomal region 1 (PAR1) and Xq21.…”
Section: The Unbiased Screening Of the Genomementioning
confidence: 99%